Bubble‐separation dynamics in a planar cyclone: Experiments and CFD simulations. Issue 7 (1st March 2018) - Xu, Xiao; Ge, Xiao‐Ling; Qian, Yun‐Dong; Wang, Hua‐Lin; Yang, Qiang
Abstract : A planar cyclone is designed for visualizing bubbles in the cross‐section of a degassing hydrocyclone. The pressure distribution is studied through a series of experiments and Reynolds stress model simulations. The velocity distribution of the planar cyclone mostly exhibits the quasi‐forced vortex zone and boundary layer zone. The bubble dynamics are simulated using both Euler‐Euler and Euler‐Lagrange approaches, and the output is compared with the imaging results. The Euler‐Euler simulation provides more accurate predictions of the bubble trajectory. The histograms of residence time and traveling distance given by the Euler‐Lagrange approach exhibit a reasonably regular pattern. With higher values of the inlet Reynolds number, stronger forces acting on the bubbles lead to a decreased but more uniform residence time. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2689–2701, 2018